Defining the medial-lateral axis of the femur: Medical imaging, conventional and functional calibration methods lead to differences in hip rotation kinematics for children with torsional deformities. (1st March 2018) - Passmore, Elyse; Graham, H. Kerr; Sangeux, Morgan
Abstract: Hip rotation during gait is a major indicator for femoral derotation osteotomy. However, repeatability of hip rotation is poor because of discrepancies in determining the medial-lateral axis of the femur. Combining 3D gait analysis with medical imaging allows in vivo evaluation of current clinical methods. We used the condylar axis, identified from low dose biplanar radiographs (EOS imaging Inc), as our reference to evaluate conventional, functional calibration and freehand 3D ultrasound methods to define the medial-lateral axis in children with lower-limb torsional deformities. Twenty participants underwent 3D gait analysis accompanied by freehand 3D ultrasound and biplanar radiographs. The condylar axis identified from biplanar radiographs provided the reference method used to construct the femoral coordinate system. This was used to evaluate a conventional, two functional calibration methods (axis transformation technique and 2DoFKnee) and freehand 3D ultrasound. We measured reliability of 3D localisation of skin markers and anatomical landmarks from the biplanar radiographs. Localisation of skin markers (SD 0.4 mm) and anatomical landmarks (SD 1.3 mm) from the biplanar radiographs were reliable, leading to a precision of 1° for the condylar axis after registration in the motion capture system. The freehand 3D ultrasound produced similar results to the biplanar radiographs reference, with internal hip rotation during gait of 18° and 19° respectively. The conventional and functional calibration methods were predominantly external compared to the reference, with average hip rotation of 4–6° internal. Freehand 3D ultrasound and biplanar radiographs provide reliable means to define the medial-lateral axis of femur for gait analysis, and aid clinical interpretation in children with torsional deformities.